A study on association between breastfeeding and its protective role against diarrhoea in under five children in a rural block of West Bengal, India - Biswas, Atanu; Mandal, Asok Kumar (International Journal Of Community Medicine And Public Health, 2016)
Background: Diarrhoea is not only one of the most common childhood illnesses, but also one of the leading causes of under nutrition and even childhood mortality globally. Breast milk is known to have protective role against childhood infections, thus preventing diarrhoea and its consequences. Methods: This cross sectional study aims to assess the pattern of breastfeeding and also episodes of diarrhoea in previous three months before the day of interview, and also the association between breastfeeding and its protective role in diarrhoea in children of less than 5 years of age. Data was collected from 81children (their mothers being respondents) and was statistically analysed using IBM SPSS (Version 20.0). Results: Only 55.6% children were exclusively breastfed up to six months or till date in children <6 months of age and 76.5% children received colostrum feeding. Thirty six children (44.4%) had at least one episode of diarrhoea in last three months. Of them 7 children had dysentery and 19 had associated vomiting. Statistical analysis shows significant association between Exclusive Breast Feeding (EBF) and colostrum feeding with its protective role in diarrhoea (P<0.01). Conclusions: Incidence of diarrhoea in last three months was higher in nonexclusively breastfed babies (86.11%) when compared to exclusively breastfed babies (11.11%). EBF has protective role against childhood infections including diarrhoea and should be promoted for awareness generation among common people.